Determination of apical constriction and apical foramen using electronic apex locator in vivo: Comparison between vital and nonvital teeth - Gaurav Aggarwal; Poonam Bogra; Saurabh Gupta; Ayushi Jindal; Nitesh Jain (Wolters Kluwer Medknow Publications, 2018)
Introduction: The aims of the present study were (1) to compare the in vivo accuracy of electronic apex locator (EAL) to locate the apical foramen and apical constriction (AC) in vital and nonvital teeth and (2) to measure and compare the distance between the AC and apical foramen based on EAL readings and those obtained by direct observation under stereomicroscope following extraction of the tooth. Materials and Methods: A sample of 40 teeth scheduled for extraction independent of the study from patients in the age range of 45-65 years was selected and divided into two groups (Group I - vital and Group II - nonvital). The AC and apical foramen were located using Root ZX II (J. Morita Corp, Kyoto, Japan) in both the groups and then by direct observation under stereomicroscope following extraction. Results: Fischer's exact test found no statistically significant difference in the ability of EAL to locate AC and apical foramen when compared between vital and nonvital teeth. Likewise, no statistically significant difference was found in the distance between the AC and apical foramen as measured by EAL in vivo and that measured by direct observation under stereomicroscope following extraction in vital (P = 0.412) and nonvital (P = 0.719) teeth (paired t-test). Conclusion: The study supports that EAL measures the location of AC and apical foramen with similar accuracy in vital and nonvital teeth. Furthermore, the distance between the two is reliable when compared with the actual distance observed under stereomicroscope supporting its widespread usage in clinical endodontics.